Unique quantitative electroencephalography differences and related behavioral dynamics in Crohn’s disease - Yihan Zhuang; Hairu Yang; Xinyi Huang; Guanghua Guo; Quan Shi; Yiting Lin; Wenwen Xue; Zeyu Huang; Sisi Zhou; Jiahui Cai; Haizhu Tan; Jing Yu (All Life)
Crohn's disease (CD) is a major type of inflammatory bowel disease (IBD) characterized by idiopathic, chronic inflammation with a patchy transmural inflammatory pattern. CD patients experience a decreased quality of life due to symptoms such as diarrhea, abdominal pain, anemia and fever. This study had a cross-sectional single-center design. The experimental group was composed of patients diagnosed with CD according to the Chinese consensus on diagnosis and treatment in inflammatory bowel disease (2018, Beijing). Fifty CD patients and 41 healthy controls were involved in this study and underwent quantitative electroencephalography (QEEG). Analysis showed that the LZC of QEEG in electrode positions O1, O2 and P4 was lower in the CD group than in the control group. Significant differences in EEG LZC were found at electrode positions F4 and P3 when comparing CD patients with a disease duration of over 10 years to those with a duration of less than 10 years. In CD, the connections between the occipital region and other brain regions may be reduced, and the dynamic behaviors may be simplified. With greater durations of CD, patients may gradually develop simplification of behavioral dynamics in particular brain regions.